2022
DOI: 10.1002/adfm.202210286
|View full text |Cite
|
Sign up to set email alerts
|

Tailoring of Photoluminescence Properties in All‐Vacuum Deposited Perovskite via Ruddlesden–Popper Faults

Abstract: Ruddlesden-Popper (RP) faults are well known in oxide perovskites, and are also observed in promising metal halide perovskites. However, the effect of RP faults on optical properties of perovskite has not been systematically investigated. In this study, it is found that RP faults are common planar faults in all-vacuum deposited CsPbBr 3 -based perovskite polycrystal thin films, and the density of RP planar faults can be greatly increased by non-stoichiometric composition (Cs-rich) as well as reduced dimensiona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 40 publications
1
1
0
Order By: Relevance
“…Region A showcases a typical [CsBr]–[CsBr] rock-salt stacking pattern that exhibits notable cracking along the RP fault planes. This configuration has been previously reported both in pure CsPbBr 3 perovskites , and various alloyed perovskites. , Prior studies have indicated that such an arrangement does not introduce deep-level defects within the perovskites. ,, This observation is consistent with our analysis, as this configuration does not contain the cation antisite defects or V Br defects that we previously identified as deep-level defects. The intrinsic driving force for crack formation in this configuration lies in the disruption of the local charge equilibrium.…”
Section: Resultssupporting
confidence: 93%
“…Region A showcases a typical [CsBr]–[CsBr] rock-salt stacking pattern that exhibits notable cracking along the RP fault planes. This configuration has been previously reported both in pure CsPbBr 3 perovskites , and various alloyed perovskites. , Prior studies have indicated that such an arrangement does not introduce deep-level defects within the perovskites. ,, This observation is consistent with our analysis, as this configuration does not contain the cation antisite defects or V Br defects that we previously identified as deep-level defects. The intrinsic driving force for crack formation in this configuration lies in the disruption of the local charge equilibrium.…”
Section: Resultssupporting
confidence: 93%
“…Lead halide perovskites have emerged as promising candidates for next-generation optoelectronic devices, including solar cells, lasers, and light-emitting diodes (LEDs). Vacuum-deposited perovskite light-emitting diodes (PeLEDs) have recently demonstrated an improved external quantum efficiency of 16.4%, which is encouraging considering the limited work done so far. Moreover, they have been integrated with thin-film transistor backplanes to fabricate active-matrix PeLED displays.…”
Section: Introductionmentioning
confidence: 99%